PENJAMINAN MUTU PENDIDIKAN ISLAM DI SEKOLAH TINGGI AGAMA ISLAM TAPANULI (STAITA) PADANGSIDIMPUAN - Linda Erawati Siregar; Zulamri Zulamri (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
Many factors cause the quality of higher education to be low, one of which is the non-implementation of higher education quality assurance. Quality assurance itself should be a separate system that ensures the continuity of quality higher education. So important is this quality assurance that STAITA Padangsidimpuan also plays a role and participates in improving the quality of its education so that the quality of education at STAITA Padangsidimpuan is able to compete with other universities and has a vision and mission as well as characteristics so that the pure goals of what are to be achieved can be achieved.Â This study uses a qualitative method, because it intends to explain the improvement of the quality of Islamic education through quality assurance activities at universities. Data collection is using interview, observation and documentation techniques. To ensure the validity of the data collected, that is by doing a pol- ulation (cross-checking of data) between methods, both interview data with observation, and documentation, as well as interview data from various informants.Â The Process of Quality Assurance of Islamic Education at the Tapanuli Padangsidimpuan Islamic High School with several standards, namely: Graduate Competency Standards, Learning Process Standards, Learning Content Standards, Learning Assessment/evaluation Standards, Lecturer and Education Personnel Standards, Management Standards, Learning Financing Standards, Outcomes Standards Research, Research Process Standards, Research Standards, Research Management Standards, Service Outcomes Standards, Service Assessment Standards, Service Financing Standards, Research Cooperation Standards, Information Systems Standards, Cooperation Standards